Effect of Queen Cell Cup Types on Graft Acceptance And Queen Bee Emergence in Apis mellifera L. - Poudel, Anisha; Pokhrel, Min Raj; Pokhrel, Govinda Prasad; Aryal, Bhawana (Journal of the Plant Protection Society, 2024)
Quality queen production is crucial for the multiplication of colonies, hive, and apiary management. A study was conducted at the Beekeeping Development Center, Bhandara, Chitwan, Nepal from April to June 2023 to assess the effectiveness queen cell cup types on grafted larvae acceptance by the workers for rearing and quality of the queen emerged. The experiment comprised four queen cell cup types as the treatments—made from bee wax (T1), paraffin (T2), blend of bee wax and paraffin (T3), and plastic cups (T4)—replicated across five queenless colonies considering randomized complete block design. Two-day-old larvae were grafted onto queen cell cups fitted on grafting frames and larval acceptance was checked after 72 hours. The quality of queen emerged across the type of cup cells was assessed considering queen quality attributes. Results indicated that mean larval acceptance was significantly higher in bee wax cells throughout the three months while acceptance was lowest in paraffin cell. The acceptance across wax-paraffin mix and plastic cup cell was moderate. The number of queen bees emerged from bee wax cups was significantly higher and displayed greater body weight and length as compared to other cell cup types. This study reveals bee wax cell cups are more suitable for worker larvae grafting for queen production in Apis mellifera.